2015
DOI: 10.1371/journal.pone.0131967
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Single Nucleotide Polymorphisms (SNPs) for High-Resolution Subtyping of Shiga-Toxin Producing Escherichia coli (STEC) O157:H7

Abstract: The objective of this study was to develop a canonical, parsimoniously-informative SNP panel for subtyping Shiga-toxin producing Escherichia coli (STEC) O157:H7 that would be consistent with epidemiological, PFGE, and MLVA clustering of human specimens. Our group had previously identified 906 putative discriminatory SNPs, which were pared down to 391 SNPs based on their prevalence in a test set. The 391 SNPs were screened using a high-throughput form of TaqMan PCR against a set of clinical isolates that repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Since a SNP set for classifying clade 8 strains into subclades 8a and 8b was not available [ 20 ], a SNP set for this study was constructed as follows. Griffing et al [ 28 ] developed a SNP set for epidemiological molecular subtyping of O157 strains using SNPs at 32 loci. This typing divided clade 8 strains into two subgroups.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since a SNP set for classifying clade 8 strains into subclades 8a and 8b was not available [ 20 ], a SNP set for this study was constructed as follows. Griffing et al [ 28 ] developed a SNP set for epidemiological molecular subtyping of O157 strains using SNPs at 32 loci. This typing divided clade 8 strains into two subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…This typing divided clade 8 strains into two subgroups. Several SNPs were selected from 32 SNPs used by Griffing et al [ 28 ] to construct the SNP set for this study. To select these several SNPs, the SNPs at 32 loci used by Griffing et al [ 28 ] were investigated using clade 8 strains with various genetic features (i.e., the various distribution of IS 629 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No specific virulence pattern distinguished the outbreak strains from sporadic strains (Berenger et al, 2015 ). Recent studies have expanded WGS typing to globally distributed strains and identified geographical genomic structuring based on distribution of stx -converting phage integration sites and SNPs (Mellor et al, 2015 ; Strachan et al, 2015 ) and provided a more detailed subtyping of E. coli O157:H7 (Griffing et al, 2015 ). However, clarity can also be gained by comparing closely related isolates to each other, rather than to reference strains (Leopold et al, 2009 ; Turabelidze et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%